Ross Ice Shelf Cavity Ocean Data - Stevens, Craig; Brewer, Mike; Grant, Brett (SEANOE, 2017)
Here we provide data from the Ross Ice Shelf ocean cavity. Location - The HWD2 Camp was established in October of 2017 at 80o 39.497’S, 174o 27.678’E where the ice is moving seaward at around ~600 m a-1 and is sourced from the Transantarctic Mountains. Profiling Instruments - Profiling was primarily conducted with an RBR Concerto CTD (conductivity-temperature depth) profiling instrument, and this was cross-calibrated against irregular profiles with an RBR Duet (pressure and temperature only), a SBE37 MicroCat CTD as well as moored SBE37 MicroCat CTDs. The RBR unit is small and has suitable sensor capability (temperature and conductivity accuracies of ±0.002°C and ±0.003 mS cm-1). Its conductivity cell design is not prone to fouling by ice crystals, making it ideal for work in the sometimes crystal-laden borehole conditions. We were inconsistent in how we mounted the CTD on its protective frame and this appeared to make small difference in the conductivity signal (resulting in an ~0.03 psu variation). This was post-corrected based on the essentially invariant mooring data from the lower water column as well as SBE37 cross-calibration profile data. Because of the potential for sediment contamination of the sensors, the profiles were mostly conservative in their proximity to the sea floor. On several occasions, profiles were conducted all the way to the sea floor. The temperature and salinity are presented in EOS-80 in order to compare with available data. Eighty three profiles are provided here (ctd_HWD2_*.dat). In addition, limited microstructure profiling was conducted to provide insight into some of the mixing details. The profiles were conducted by lowering the instrument to the ice base then commencing a sequence of three up-down “yo-yos” before returning to the surface and downloading. A data segment is included here (VMP_HWD2.dat). There were some challenges registering the vertical coordinate for the profiles. The melting of the borehole generates a trapped pool of relatively fresh water. The interface ...